2013
DOI: 10.1371/journal.pone.0081889
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Inflammatory Responses with Microfluidic Immunoblotting

Abstract: Rapid profiling of signaling pathways has been a long sought after goal in biological sciences and clinical medicine. To understand these signaling pathways, their protein components must be profiled. The protein components of signaling pathways are typically profiled with protein immunoblotting. Protein immunoblotting is a powerful technique but has several limitations including the large sample requirements, high amounts of antibody, and limitations in assay throughput. To overcome some of these limitations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Previous studies have reported that the hydrodynamic, electrical, and acoustic are the most popular tools for particle manipulation explained in CRISPR/Cas studies [85]. Additionally, microfluidics has been used for the detection of proteins (e.g., microfluidic western blotting), nucleic acids (e.g., PCR, direct detection, and DNA sequencing of nucleic acids on microfluidic chips), single cells, specific organs (organ-on-a-chip), and clinically critical small molecules [86][87][88].…”
Section: Microfluidic Methods and Clinical Applicationsmentioning
confidence: 99%
“…Previous studies have reported that the hydrodynamic, electrical, and acoustic are the most popular tools for particle manipulation explained in CRISPR/Cas studies [85]. Additionally, microfluidics has been used for the detection of proteins (e.g., microfluidic western blotting), nucleic acids (e.g., PCR, direct detection, and DNA sequencing of nucleic acids on microfluidic chips), single cells, specific organs (organ-on-a-chip), and clinically critical small molecules [86][87][88].…”
Section: Microfluidic Methods and Clinical Applicationsmentioning
confidence: 99%
“…A PDMS microfluidic network was subsequently assembled onto the PVDF membrane with each microchannel delivering a primary antibody solution ( Figure a). This microfluidic blotting enables simultaneous analysis of multiple proteins from a single sample, and it consumes significant less antibody (≈1% of conventional WB) . We subsequently improved the system by adopting a serpentine network of parallel microfluidic channels to make it amendable for multi‐lane blotting.…”
Section: Microfluidics‐based Bioanalysismentioning
confidence: 99%
“…Therefore, specimens should be measured alongside controls with known concentrations of the cytokines in question (32). Finally, exciting research opportunities now exist using nano-and microfluidic technology for low volume, point of care measurement of a number of inflammatory cytokines (33,34).While still in the research domain, these newest techniques show the most promise of these cytokines to be measured as part of routine patient care, the ultimate "bench to bedside" scenario.…”
Section: When Are Pards Biomarkers Best Measured?mentioning
confidence: 99%